Cancer-associated financial burden in German head and neck cancer patients - Rast, Jonas; Zebralla, Veit; Dietz, Andreas; Wichmann, Gunnar; Wiegand, Susanne (Frontiers in Oncology, 2024)
Background The financial toxicity of cancer causes higher morbidity and mortality. As the financial burden due to head and neck cancer (HNC) in European healthcare systems with legally established compulsory health insurance is still poorly understood, we set up an investigation to assess the financial impact of HNC. Methods Between August 2022 and March 2023, HNC consecutive patients (n = 209) attending the cancer aftercare program of a university hospital in an outpatient setting were surveyed utilizing self-administered questionnaires about their socioeconomic situation, income loss, and out-of-pocket payments (OOPPs). Results The majority of HNC patients (n = 119, 59.5%) reported significant financial burden as a consequence of OOPP (n = 100, 50.0%) and/or income loss (n = 51, 25.5%). HNC patients reporting financial burden due to OOPP had on average 1,716 € per year costs related to their disease, whereas patients reporting an income loss had a mean monthly income loss of 620.53 €. Advanced UICC (7th edition, 2017) stage, T3 or T4 category, and larynx/hypopharynx cancer are significant predictors of financial burden. Conclusion HNC survivors suffer from significant financial burden after HNC treatment, even in Germany with a healthcare system with statutory health insurance. The findings from this study offer valuable insights for healthcare professionals and policymakers, helping them acknowledge the economic impact of HNC.